2018
DOI: 10.5194/essd-2018-23
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general database of hydrometeor single scattering properties at microwave and sub-millimetre wavelengths

Abstract: Abstract. A main limitation today in simulations and inversions of microwave observations of ice hydrometeors (cloud ice, snow, hail . . . ) is the lack of data describing the interaction between electromagnetic waves and the particles. To improve the situation, the development of a comprehensive dataset of such "scattering properties" has been started. The database aims at giving a broad coverage in both frequency (1 to 886 GHz) and temperature (190 to 270 K), to support both passive and active current and pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Notice that we include some of the single crystals (p‐13, p‐29, and p‐44) from K16 (dark gray upward triangles) to demonstrate that the measured values toward the upper left part of the diagram could be explained by single crystals in random orientation. Some of the single crystals in Eriksson et al () also occupy this area (not shown here). The physical aggregate models (upper left panel) seem to propagate to the upper middle part of the diagram as the size increases, and showing a maximum in DFR Ka / W at 7–9 dB.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Notice that we include some of the single crystals (p‐13, p‐29, and p‐44) from K16 (dark gray upward triangles) to demonstrate that the measured values toward the upper left part of the diagram could be explained by single crystals in random orientation. Some of the single crystals in Eriksson et al () also occupy this area (not shown here). The physical aggregate models (upper left panel) seem to propagate to the upper middle part of the diagram as the size increases, and showing a maximum in DFR Ka / W at 7–9 dB.…”
Section: Resultsmentioning
confidence: 63%
“…"> 7.J16: Johnson et al () (available from the Author): melted aggregates of dendrites with melted mass fraction 0% (J16a), 10% (J16b), and 70% (J16c) E18: Eriksson et al () (available at ARTS database ()): aggregates of hexagonal columns with 100 (E18a) and 350 (E18b)‐μm‐sized monomers aggregates of hexagonal plates with 100 (E18c) and 350 (E18d)‐μm‐sized monomers aggregates of hexagonal blocks with 100 (E18e) and 350 (E18f)‐μm‐sized monomers 9.T18: This study (available at FMI ()): fractals with f d = 1.6 (T18a), 2.0 (T18b), 2.4 (T18c), and 2.8 (T18d)…”
Section: Microphysical Models Of Snowmentioning
confidence: 99%
See 1 more Smart Citation
“…In the RT for MW, a different Table 9. Modification introduced in the radiative transfer model settings for microwave instruments in terms of particle shape (Scattering type) from database ARTS (Eriksson et al, 2018).…”
mentioning
confidence: 99%